Hiperglicemia induz hiperalgesia mecânica e despolarização do potencial de repouso da membrana de neurônios nociceptivos primários: papel dos canais de potássio sensíveis ao ATP - Lima, Taís de Campos (2018)
Introduction: Diabetes is a group of metabolic diseases characterized by hyperglycemia, which is growing and relevant problem for public health. Chronic hyperglycemia eventually results in the development of diabetic neuropathy, which often causes chronic pain, difficult to treat. The mechanisms responsible for the development of painful diabetic neuropathy are not well known, but some studies suggest that alterations in ion channels expressed by nociceptive neurons might be involved. Objectives: To study the direct effect of hyperglycemia on the resting membrane potential of primary nociceptive neurons and the nociceptive mechanical threshold in rats. To investigate the involvement of potassium channels sensitive to ATP (K+ATP) in this process. Material and methods: Variations in membrane potential were recorded by confocal microscopy using the fluorescence variation emitted by primary cultured neurons of the dorsal root ganglia in the presence of the fluorescent indicator DiBAC4(3). It was tested the effect of different glucose concentrations, insulin, the K+ATP channel blocker glibenclamide, and the K+ATP channel activator diazoxide. The mechanical sensitivity threshold of rats treated in vivo with intraganglionar injection (L5) of different concentrations of glucose, mannitol and diazoxide was evaluated using the electronic von Frey test. Results: High glucose concentrations (300, 450 and 600 mg/dL) induced depolarization of dorsal root ganglion neurons in culture in a concentrationdependent manner. Changes in resting membrane potential were not due to the addition of a hyperosmotic solution, which was tested by the administration of an isosmotic glucose solution (600 mg/dL). In vitro, insulin administration (1 μM) inhibited glucose-induced depolarization as well as diazoxide (10 μM), a K+ATP channel openner. Glibenclamide (10 μM), a K+ATP channel blocker, caused depolarization of cultured neurons. Intraganglionar injection (L5) of high concentrations of glucose, in vivo, induced a state of hyperalgesia detected by a reduced mechanical threshold. Co-administration of diazoxide (10 μM) inhibited glucose induced hyperalgesia. Injection of hyperosmotic solution of mannitol, which is metabolically inert, did not cause changes in the mechanical threshold, indicating that changes in osmolarity are not responsible for the effect of glucose in vivo. Conclusion: Results suggest that closure K+ATP channels expressed in peripheral sensory neurons are responsible for a direct glucose effect on nociceptive neurons and, therefore, might be involved in the development of diabetic painful neuropathy. Since sulfonylureas (like glibenclamide, for example) that act by blocking K+ATP are used to treat type 2 diabeticpatients, it is important to evaluate possible side effects of such drugs at primary sensory neurons.